Multifunctional Fe3O4@SiO2 nanoparticles for selective detection and removal of Hg2+ ion in aqueous solution1. Issue 15 (25th February 2015) - Sun, Zebin; Guo, Dan; Li, Haizhen; Zhang, Li; Yang, Bo; Yan, Shiqiang
<x xml:space="preserve">Abstract</x> A multifunctional magnetic core–shell Fe3O4@SiO2 nanoparticle decorated with rhodamine-based receptor has been successfully synthesized, aiming to detect and remove Hg2+ from aqueous media.